When Does Irl Matter? Location And Networked Creativity In Gamer, Hacker And Maker Publics - Braybrooke, Kat; Annika, Richterich; Karin, Wenz; Tim, Jordan (AoIR Selected Papers of Internet Research, 2017)
This panel examines how communities engaged in digital practices rely on offline and online environments to maintain their networks. We argue that understanding how these kinds of spaces are used for private and public interaction is crucial in order to make sense of the networked practices of digitally grounded communities. Through four papers, we analyse gamer, hacker, and maker cultures as examples of networked actors known to rely on and create digital technologies. To what extent do networked publics require collocation (Trainer et al. 2016), i.e. physical co-presence more casually referred to as IRL, and direct face-to-face interaction? We ask whether ‘networked publics’, i.e. the concept that power in a society is exercised through the machinations of networks (Castells 2011), need to take greater account of co-located activities among what are heavily ‘digitised’ groups. We examine ‘online founded’ groups of hackers and gamers, both of which generate their own sense of what they make public and private. We then explore communities of makers who are heavily afforded by networked technologies but, unlike gamers and hackers, require physical collocation to create their public/private divides. We address two main, interrelated questions: What are the main factors in facilitation that a community focuses on to move between online interaction and collocation (and is this a false binary)? What kinds of practices and motivations foster an interest in combining digital and physical collaboration? This panel will reflect on the role of institutions, corporations, Internet technologies, and communities themselves in defining these choices. Particularly, we will explore − through the effects of face-to-face elements across the groups we are studying − how they create not just a sense of being a networked public, but one that this is complexly constructed out of a number of different public/private divides. In particular, the way collocation is integrated is different across the groups this panel studies, and these differences point to ways that each group is constituted by a number of ways, dividing public and private. The ongoing location of a FabLab contrasts with a ‘pop up’ makerspace in a cultural institution. The episodic collocation afforded by an annual conference contrasts with regular meetups of hackers in similar regions. These developments point to a more complex and fluid vision of networked publics in which it is important to trace multiple public/private divides and how they integrate online and offline interactions. Two challenges will be posed through this examination of cases and abovementioned current theories of networked publics. First, we will examine how collocation or physical connection remains a structuring element in different networked publics, and why this has been under-appreciated and theorised. Second, grasping the roles of collocation, we will make it clear that when discussing networked publics, it is important to be explicit that this is a public/private relationship that is continually created and re-created, and that each group is constituted by not just one such divide, but several.